Better Writing in Scientific Publications Builds Reader Confidence and Understanding - Ryba, Ren; Doubleday, Zoë A.; Dry, Matthew J.; Semmler, Carolyn; Connell, Sean D. (Frontiers in Psychology, 2021)
Scientific publications are the building blocks of discovery and collaboration, but their impact is limited by the style in which they are traditionally written. Recently, many authors have called for a switch to an engaging, accessible writing style. Here, we experimentally test how readers respond to such a style. We hypothesized that scientific abstracts written in a more accessible style would improve readers’ reported readability and confidence as well as their understanding, assessed using multiple-choice questions on the content. We created a series of scientific abstracts, corresponding to real publications on three scientific topics at four levels of difficulty – varying from the difficult, traditional style to an engaging, accessible style. We gave these abstracts to a team of readers consisting of 170 third-year undergraduate students. Then, we posed questions to measure the readers’ readability, confidence, and understanding with the content. The scientific abstracts written in a more accessible style resulted in higher readability, understanding, and confidence. These findings demonstrate that rethinking the way we communicate our science may empower a more collaborative and diverse industry.